Literary-Based Stylistic Devices In Linguocultural Competence Development - Bibizhan Begmanova, Zhanar Talaspayeva,, Nurzhanat Rakhmanova, Baglan Bazylova, Bibigul Sultanova, (Opción, 2019)
The aim of the article is to prove that comparative analysis of metaphors as a literary-based stylistic device in different languages helps to develop linguacultural competence at all levels of language education of the Republic of Kazakhstan via comparative qualitative research methods. The analysis of the received results presented in the work allows revealing the pedagogical potential of metaphors in developing linguocultural competence at all levels of linguistic education. In conclusion, the main global spheres of metaphors are life, time, wealth, love and happiness.